DOI: 10.11606/d.41.2010.tde-07122010-153331
|View full text |Cite
|
Sign up to set email alerts
|

Diferenciação geográfica de Ecpleopus gaudichaudii (Squamata, Gymnophthalmidae) baseada em caracteres morfológicos e moleculares, e considerações sobre a descrição osteológica

Abstract: Minha avó, a pessoa mais sábia que eu conheci, Que me deu uma grande lição de vida, E que, tenho certeza, me acompanha onde quer que esteja.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 93 publications
0
1
0
Order By: Relevance
“…However, recent molecular studies have indicated that it has greater taxonomic complexity. The evidence suggests that the name E. gaudichaudi may not apply to individuals in Minas Gerais and that there could soon be a new revision of the genus (Carolino 2010). This species was considered rare until a few years ago (Eisemberg et al 2004), but expansion of the collection efforts has shown that this species is common, as reported by Dixo & Verdade (2006) in forested areas of the Morro Grande Forest Reserve in Cotia, São Paulo, in which 54% of the lizards caught belonged to this species.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent molecular studies have indicated that it has greater taxonomic complexity. The evidence suggests that the name E. gaudichaudi may not apply to individuals in Minas Gerais and that there could soon be a new revision of the genus (Carolino 2010). This species was considered rare until a few years ago (Eisemberg et al 2004), but expansion of the collection efforts has shown that this species is common, as reported by Dixo & Verdade (2006) in forested areas of the Morro Grande Forest Reserve in Cotia, São Paulo, in which 54% of the lizards caught belonged to this species.…”
Section: Discussionmentioning
confidence: 99%